Evaluation of an immunochemical test kit for polychlorinated biphenyls in soils and comparison with gas chromatographic analysis - Pullen, Sonja; Haiber, Georg; Schöler, Heinz Friedrich; Hock, Bertold (International journal of environmental analytical chemistry, 1996)
The commercial immunochemical test kit Drager EnviCheck PCB for the determination of polychlorinated biphenyl concentrations in soil was evaluated, and the results were validated by GC-ECD measurement. Four different types of soil were spiked with different concentrations of the PCB mixture Clophen A40 and analyzed by either of the methods. The test was carried out as a direct competitive enzyme immunoassay in test tubes. The test kit classified three different groups of PCB concentrations in soil: “less than 1 mg/kg soil”, “between 1 and 10 mg/kg soil”, and “at least 10 mg/kg soil”. The results produced by the test kit showed a good intra-and inter-assay reproducibility and corresponded mainly with the nominal values of the fortification. Soils with a high content of organic matter produced a slight overestimation. False-negative determinations did not occur. GC-ECD measurement showed a good correspondence with the results of the test kit and the spiked PCB values.